New Familiar Abenakis and English Dialogues - Day, Gordon M.; Laurent, Stephen (1957)
A reading of Joseph Laurent's "New Familiar Abenakis and English Dialogues" (St-Francis, Quebec, 1884). The author was a chief of the Abenakis Indians at the village of St. Francis, Quebec. The reader is the son of the author. Recorded in New Hampshire in 1957.